NIETZSCHE VERSUS GADAMER : “MEANING” AS A PROBLEM OF DOGMATISM AND RELATIVISM - Mickevičius, Arūnas (Problemos, 2017)
The article aims to show the similarities and differences between Nietzsche’s interpretative knowledge and Gadamer’s interpretative understanding. Emphasizing the “interpretative” nature of knowledge and understanding both authors faced the problem: how is it possible to avoid the dogmatic affirmation of one and only “correct” interpretation without lapsing into absolute relativism, which rejects any possibility of speaking about “validity” of competing interpretations. The dilemma of dogmatism and relativism in understanding of “meaning” is also the central problem of modern hermeneutics that had sparkled the debate between H. G. Gadamer and E. Betti, J. Derrida and J. Habermas. This article is intended to support two theses. First, there are irreducible differences between positions of Nietzsche and Gadamer, therefore, any attempts to reduce Nietzsche’s “perspectivism” to Gadamer’s “philosophical hermeneutics” are not valid. Second, the problem of relativism and dogmatism of “meaning” in Gadamer’s hermeneutics can be solved through the provision of Husserl’s phenomenology, which describes how we recognize the meaning of a “thing” as a “thing in itself” through different “profiles”. However, Nietzsche’s perspectivism, which criticizes dogmatism of “meaning”, does not solve the problem and hence slides to the other extreme – relativism.
Keywords: Nietzsche; Gadamer; interpretation; hermeneutical understanding; meaning; relativism; dogmatism; perspectivism